Type-specific molecular signaling architectures and synaptic plasticity of Drosophila olfactory sensory neurons - Acharya, Namrata; Wiesel, Eric; Selcho, Mareike; Ehmann, Nadine; Lamberty, Marius; Hansson, Bill S.; Wicher, Dieter; Kittel, Robert J. (Frontiers in Cellular Neuroscience, 2025)
Olfactory sensory neurons (OSNs) detect odours at a wide range of intensities. In Drosophila, volatile compounds bind to specific odorant receptors (ORs), which tune the sensitivity of chemoreception. To test whether additional mechanisms underlie odour-specific neuronal processing, we analysed the spatial distribution of ORs in dendrites and investigated OSN synapses in the antennal lobe, the first relay station of the olfactory pathway. Here, we studied the molecular structure and plasticity of the presynaptic active zone (AZ), the specialized site of neurotransmitter release. We focused on a highly sensitive OSN type that expresses the receptor Or56a and is exclusively activated by geosmin, an odorant signalling ecologically harmful microorganisms. Our results uncover a differential arrangement of dendritic ORs and core AZ proteins in alarm odour-detecting Or56a compared to conventional food-odour detecting OSNs. Interestingly, the data also show that Or56a OSNs display a limited capacity for homeostatic plasticity in response to a genetic reduction of presynaptic release probability. We hypothesise that this feature reflects the basal tuning of geosmin-sensing neurons towards maximum levels of performance.